2021
DOI: 10.3389/fphar.2021.638210
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Alkaloids: Novel Bioactive Natural Products From Lobelia Species

Abstract: In this work, we reviewed the progress in the phytochemical and biological investigations of bioactive components derived from medicinally valuable Lobelia species. In the last 60 years, Lobelia has garnered significant attention from the phytochemist from around the world, majorly due to the discovery of bioactive piperidine alkaloids (e.g., lobinaline and lobeline) in the early 1950s. Later, lobeline underwent clinical trials for several indications including the treatment of attention deficit hyperactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
3
8
0
Order By: Relevance
“…Numerous investigations have shown that lobeline has a variety of pharmacological effects on the CNS (reviewed in Reference 46). Interestingly, lobeline shares 73% structural similarity and several common pharmacophoric features like aromatic rings, an ionizable moiety and a hydrophobic surface with donepezil, a well‐known AChE inhibitor (Figure 1a–d and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous investigations have shown that lobeline has a variety of pharmacological effects on the CNS (reviewed in Reference 46). Interestingly, lobeline shares 73% structural similarity and several common pharmacophoric features like aromatic rings, an ionizable moiety and a hydrophobic surface with donepezil, a well‐known AChE inhibitor (Figure 1a–d and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…First, the proper mechanism by which pH induced isomerization should be revealed. Secondly, the study of isomer activity should not be limited to nAChRs receptors, nor should it be restricted to the excitatory respiration effect [ 26 ]. Last but not the least, the study of the structure–activity relationship of trans -lobeline should be considered in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…East Asian lobelias are traditional medicinal plant species because of their bioactivity and many chemical constituents (Anand et al, 2009;Han et al, 2013;Zheng et al, 2021). However, the scarcity of genomic resources for East Asian lobelias has hampered plant genetics, ecology, taxonomy, and resource utilization.…”
Section: Molecular Markersmentioning
confidence: 99%
“…Valuable medicines with anti-inflammatory, antioxidative, antiviral, and antiepileptic functions can be made from lobeline and its derivatives (Tamboli et al, 2012;Thawabteh et al, 2019). Lobeline is predominantly derived from plants of the Lobelia (Lammers, 2007b;Zheng et al, 2021). Lobelia L. is the largest genus among all the 29 genera in the subfamily Lobelioideae (Campanulaceae) and has an almost cosmopolitan distribution mainly in tropical to warm-temperate climate regions (Lammers, 2007a;Lammers, 2011).…”
Section: Introductionmentioning
confidence: 99%